Dynamics of the human skin mediator lipidome in response to dietary ω‐3 fatty acid supplementation. Issue 11 (13th September 2019) - Kendall, Alexandra C.; Pilkington, Suzanne M.; Murphy, Sharon A.; Carratore, Francesco Del; Sunarwidhi, Anggit L.; Kiezel‐Tsugunova, Magdalena; Urquhart, Paula; Watson, Rachel E. B.; Breitling, Rainer; Rhodes, Lesley E.; Nicolaou, Anna
Abstract : Nutritional supplementation with fish oil or ω‐3 (n‐3) polyunsaturated fatty acids (PUFAs) has potential benefits for skin inflammation. Although the differential metabolism of the main n‐3PUFA eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) could lead to distinct activities, there are no clinical studies comparing their relative efficacy in human skin. Following a 10‐wk oral supplementation of healthy volunteers and using mass spectrometry‐based lipidomics, we found that n‐3PUFA mainly affected the epidermal mediator lipidome. EPA was more efficient than DHA in reducing production of arachidonic acid–derived lipids, and both n‐3PUFA lowered N ‐acyl ethanolamines. In UV radiation–challenged skin (3 times the minimum erythemal dose), EPA attenuated the production of proinflammatory lipids, whereas DHA abrogated the migration of Langerhans cells, as assessed by immunohistochemistry. Interestingly, n‐3PUFA increased the infiltration of CD4 + and CD8 + T cells but did not alter the erythemal response, either the sunburn threshold or the resolution of erythema, as assessed by spectrophotometric hemoglobin index readings. As EPA and DHA differentially impact cutaneous inflammation through changes in the network of epidermal lipids and dendritic and infiltrating immune cells, they should be considered separately when designing interventions for cutaneous disease.—Kendall, A. C., Pilkington, S. M., Murphy, S. A., Del Carratore, F., Sunarwidhi, A. L., Kiezel‐Tsugunova, M., Urquhart, P., Watson, R. E. B., Breitling, R., Rhodes, L. E., Nicolaou, A. Dynamics of the human skin mediator lipidome in response to dietary ω‐3 fatty acid supplementation. FASEB J. 33, 13014–13027 (2019). www.fasebj.org